Design and Synthesis of Arylboronic Acid Chemosensors for the Fluorescent-Thin Layer Chromatography (f-TLC) Detection of Mycolactone - Gideon Atinga Akolgo; Benjamin M. Partridge; Timothy D. Craggs; Kingsley Bampoe Asiedu; Richard Kwamla Amewu (Chemosensors, 2025)
Fluorescent chemosensors are increasingly becoming relevant in recognition chemistry due to their sensitivity, selectivity, fast response time, real-time detection capability, and low cost. Boronic acids have been reported for the recognition of mycolactone, the cytotoxin responsible for tissue damage in Buruli ulcer disease. A library of fluorescent arylboronic acid chemosensors with various signaling moieties with certain beneficial photophysical characteristics (i.e., aminoacridine, aminoquinoline, azo, BODIPY, coumarin, fluorescein, and rhodamine variants) and a recognition moiety (i.e., boronic acid unit) were rationally designed and synthesised using combinatorial approaches, purified, and fully characterised using a set of complementary spectrometric and spectroscopic techniques such as NMR, LC-MS, FT-IR, and X-ray crystallography. In addition, a complete set of basic photophysical quantities such as absorption maxima (λabsmax), emission maxima (λemmax), Stokes shift (∆λ), molar extinction coefficient (ε), fluorescence quantum yield (ΦF), and brightness were determined using UV-vis absorption and fluorescence emission spectroscopy techniques. The synthesised arylboronic acid chemosensors were investigated as chemosensors for mycolactone detection using the fluorescent-thin layer chromatography (f-TLC) method. Compound 7 (with a coumarin core) emerged the best (λabsmax = 456 nm, λemmax = 590 nm, ∆λ = 134 nm, ε = 52816 M−1cm−1, ΦF = 0.78, and brightness = 41,197 M−1cm−1).